دور أحمد بن محمد بن موسى الرازي في التدوين والكتابة التاريخية في الأندلس - مهدي, لميس ليث (lark, 2018)
This study is an attempt to discuss the Arabs and the Muslims role in writing history in Muslim Spain which was also called Al-Andalus. This subject, however, is a very wide one, therefore, a quick survey is given of the rise and development of the historical writing in Muslim Spain and the principal historians. Then the study concentrates on one developed stage in which the family of Al-Razi emerged as factor in developing the writing of history. Ahmad Al-Razi, in particular, who is the main member of the family because of his voluminous output in the field of history.